In vivo Ultrasonographic Evaluation of Patellar Tendon Stiffness after Anterior Cruciate Ligament Reconstruction with Patellar Tendon Autograft - Hsin-Yi Liu; Troy Blackburn; Darin Padua; R. Alexander Creighton; Paul Weinhold (Applied Bionics and Biomechanics)
Background: Tendon mechanical properties have been used to evaluate the effects of therapies on the healing of animal tendons, but these measures have not been convenient to record in vivo in humans due to their invasive nature. The aims of this study were to assess the capability of an ultrasonography technique to track the change in stiffness of the healing human patellar tendon and to assess the correlation between stiffness parameters and clinical recovery measurements.